An adenovirus-vectored RVF vaccine confers complete protection against lethal RVFV challenge in A129 mice - Hao, Meng; Bian, Ting; Fu, Guangcheng; Chen, Yi; Fang, Ting; Zhao, Chuanyi; Liu, Shuling; Yu, Changming; Li, Jianmin; Chen, Wei (Frontiers in Microbiology, 2023)
Rift valley fever virus (RVFV) is a mosquito-transmitted bunyavirus that causes severe disease in animals and humans. However, there is currently no vaccine approved for human use to prevent RVFV infection, and commercialized veterinary vaccines do not optimally combine efficacy with safety. We generated Ad5-GnGc, a replication-incompetent recombinant Ad5 vector (human adenovirus serotype 5) expressing codon-optimized RVFV glycoproteins Gn and Gc, and evaluated its immunogenicity in mice. Intramuscular immunization of Ad5-GnGc induces strong and durable antibody production and robust cellular immune responses in mice. Additionally, a single low dose of 106 IFU Ad5-GnGc vaccination can completely protect interferon-α/β receptor-deficient A129 mice from lethal RVFV infection. Our results suggest that Ad5-GnGc is a promising vaccine candidate against RVFV, supporting its development for animal and human vaccination.